Effect of hand placement position on press-to-handstand techniques and stability - Kong, P. W.; Leung, S. Y.; Han, Y. S. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Considerable variations in hand placement positions are seen among gymnasts when executing a press-to-handstand. The purpose of this study was to investigate the effect of hand placement position on press-to-handstand techniques and stability. Three male gymnasts performed two press-to-handstands in different hand positions (fingers pointing forward and outward) on a force platform. Postural sway variables were measured to assess stability. Video recordings were taken to obtain temporal and kinematic measurements. Results showed pressing to handstand in fingers outward position was characterized by less postural sway, less extended body alignment and a more under-rotated handstand orientation. These can be seen strategies to adjust the centre of mass towards a more anterior position to avoid over-rotation.